DIGITAL STORYTELLING AS A COLLABORATIVE WRITING PROJECT AMONG EFL LEARNERS : A Case Study in One Junior High School in Bandung - Aninditya Putri Nugroho, - (2017)
In this 21st century, language learning and teaching nowadays has moved towards the digital classroom with the use of technology. Digital technologies are being used in the classroom in order to provide a new learning environment for the students. With the combination of digital technology and collaborative writing pedagogy, this study focuses on digital story as one tool to assist the integration of technology and also collaboration in producing a text. This study uses Language-Related Episodes (LREs) to analyze the patterns of interaction between students during their collaboration on a shared digital stories. Follow up questionnaires with the students also provides insight into their perception of their collaboration in the context of digital technology. The result of this study shows that as the students produce more LREs during the production of digital storytelling, they acquire language through peer feedback and collective scaffolding. Students can also access each other's linguistic resources and thus can make them achieve results beyond what they would have achieved on their own.